Auditory Comprehension Deficits in Post-stroke Aphasia: Neurologic and Demographic Correlates of Outcome and Recovery - Lwi, Sandy J.; Herron, Timothy J.; Curran, Brian C.; Ivanova, Maria V.; Schendel, Krista; Dronkers, Nina F.; Baldo, Juliana V. (Frontiers in Neurology, 2021)
One of the most challenging symptoms of aphasia is an impairment in auditory comprehension. The inability to understand others has a direct impact on a person’s quality of life and ability to benefit from treatment. Despite its importance, limited research has examined the recovery pattern of auditory comprehension and instead has focused on aphasia recovery more generally. Thus, little is known about the time frame for auditory comprehension recovery following stroke, and whether specific neurologic and demographic variables contribute to recovery and outcome. Methods: This study included 168 chronic left hemisphere stroke patients with auditory comprehension impairments ranging from mild to severe. Univariate and multivariate lesion-symptom mapping (LSM) was used to identify brain regions associated with auditory comprehension outcomes on three different tasks: Single-word comprehension, yes/no sentence comprehension, and comprehension of sequential commands. Demographic variables (age, gender, and education) were also examined for their role in these outcomes. In a subset of patients who completed language testing at two or more time points, we also analyzed the trajectory of recovery in auditory comprehension using survival curve-based time compression. Results: LSM analyses revealed that poor single-word auditory comprehension was associated with lesions involving the left mid- to posterior middle temporal gyrus, and portions of the angular and inferior-middle occipital gyri. Poor yes/no sentence comprehension was associated almost exclusively with the left mid-posterior middle temporal gyrus. Poor comprehension of sequential commands was associated with lesions in the left posterior middle temporal gyrus. There was a small region of convergence between the three comprehension tasks, in the very posterior portion of the left middle temporal gyrus. The recovery analysis revealed that auditory comprehension scores continued to improve beyond the first year post-stroke. Higher education was associated with better outcome on all auditory comprehension tasks. Age and gender were not associated with outcome or recovery slopes. Conclusions: The current findings suggest a critical role for the posterior left middle temporal gyrus in recovery of auditory comprehension following stroke, and that spontaneous recovery of auditory comprehension can continue well beyond the first year post-stroke.